Floating Dock with Automatic Early Detection for Tidal Mitigation and Tidal Flooding with IOT-Based Instruments - Widiyanto, Sinung; Poundra, G. A. P.; Aditya, B. K.; Suyanto, H.; Ramadhon, M. I. Z.; Prihantoro, F. H. (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: Coastal areas frequently face the threat of increasingly intense tidal and tidal flooding due to climate change and sea level rise. These conditions disrupt dock operations and endanger the safety of infrastructure and surrounding communities. To address these challenges, this research designed and developed a new system. Method: An Internet of Things (IOT)-based Automatic Early Detection Floating Dock is an adaptive mitigation solution. The system is equipped with various sensors, including ultrasonic sensors, water pressure sensors, and a GPS module, to monitor sea level in real time. Practical Applications: Collected data is automatically transmitted to an online monitoring platform using a wireless connection, enabling rapid analysis and early warnings to stakeholders. An adaptive floating mechanism allows the pier to automatically adjust its height according to changing water levels, ensuring its operational and safe operation. Conclusion: System testing demonstrated that the tool can predict potential tidal flooding early and function stably in dynamic marine conditions. This innovation not only increases the resilience of dock infrastructure but also provides direct benefits for early warning systems in coastal areas. The application of this technology is expected to be part of a long-term adaptation strategy to the impacts of climate change in coastal areas.